La razón que nos asiste a los segundos: música, política y estética en los himnos nacionales de América Latina (Estudios) - Escobar Jiménez, Christian Manuel (2015)
Apparently, in several Latin American countries the myth exits of the artistic quality of national anthems of each country,even awarding them with a prime spot in an apocryphal ranking headed by the Marseillaise, the French national anthem. From an outline of the modern concept of art, as a unique and unrepeatable expression, confronted with the idea of tópoi, the reason for such a myth and how it works perfectly in the consolidation of our national states and their republican ideal, could be explained.